The missing link: does tunnelling nanotube-based supercellularity provide a new understanding of chronic and lifestyle diseases? - Rustom, Amin (Open biology, 2016)
Tunnelling nanotubes (TNTs) are increasingly recognized as central players in a multitude of cellular mechanisms and diseases. Although their existence and functions in animal organisms are still elusive, emerging evidence suggests that they are involved in developmental processes, tissue regeneration, viral infections or pathogen transfer, stem cell differentiation, immune responses as well as initiation and progression of neurodegenerative disorders and cancer (see Sisakhtnezhad & Khosravi 2015 Eur. J. Cell Biol. 94, 429-443. (doi:10.1016/j.ejcb.2015.06.010)). A broader field of vision, including their striking functional and structural resemblance with nanotube-mediated phenomena found throughout the phylogenetic tree, from plants down to bacteria, points to a universal, conserved and tightly regulated mechanism of cellular assemblies. Based on our initial definition of TNTs as open-ended channels mediating membrane continuity between connected cells (Rustom et al. 2004 Science 303, 1007-1010. (doi:10.1126/science.1093133)), it is suggested that animal tissues represent supercellular assemblies that - besides opening discrete communication pathways - balance diverse stress factors caused by pathological changes or fluctuating physiological and environmental conditions, such as oxidative stress or nutrient shortage. By combining current knowledge about nanotube formation, intercellular transfer and communication phenomena as well as associated molecular pathways, a model evolves, predicting that the linkage between reactive oxygen species, TNT-based supercellularity and the intercellular shuttling of materials will have significant impact on diverse body functions, such as cell survival, redox/metabolic homeostasis and mitochondrial heteroplasmy. It implies that TNTs are intimately linked to the physiological and pathological state of animal cells and represent a central joint element of diverse diseases, such as neurodegenerative disorders, diabetes or cancer.